Expression of circulating miR-101 and miR-744 in nasopharyngeal carcinoma and their performance as diagnostic biomarkers - Azmir, Ahmad; Mohan, Vijaya; A., Sivanesan; Tang, Lu Ping; Tolos, Siti Marponga; Tumian, Afidalina; Abdullah, Kahairi; Kaderi, Mohd Arifin (Innovare Academic Sciences, 2018)
Our previous study showed that miR-101 and miR-744 were deregulated in nasopharyngeal carcinoma (NPC) tissues as compared to control tissues with certain diagnostic performance. Thus, we would like to observe the expression of both miRNAs in plasma of NPC patients as compared to control subjects and analyse their diagnostic performance. Plasma were collected from 33 NPC patients and 33 control subjects and subjected to total RNA extraction. Reverse transcription, pre-amplification and quantitative polymerase chain reaction (qPCR) were performed on the total RNA extract using Taqman microRNA Assays. Fold-change of the miRNAs were calculated using 2-ΔΔCq formula and statistical analyses were performed using SPSS version 20 software. The qPCR results showed that miR-101 and miR-744 (p>0.05) were up-regulated in NPC as compared to control plasma. Receiver operating characteristic curve analysis showed that area under curve (AUC) for miR-101, miR-744 and combination of miR-101 and miR744 were 0.374, 0.410 and 0.437, respectively, in discriminating NPC patients from control subjects, but they have AUC of 0.647, 0.69 and 0.599, respectively, in discriminating early from late stage NPC. The up-regulation of miR-101 and miR-744 have been reported in previous studies indicating the consistency of our findings. Although we found that they have poor diagnostic values in plasma for discriminating NPC patients from control subjects, they have better diagnostic values in discriminating early from late stage NPC. Therefore, we have successfully reported the up- regulation of miR-101 and miR-744 in plasma of NPC with respective diagnostic performance.